Microsporum canis Causes Cutaneous and Extracutaneous Feline Dermatophytic Pseudomycetomas: Molecular Identification and Clinicopathological Characteristics - Stefan Hobi; Wing Yan Jacqueline Tam; May Tse; Omid Nekouei; Yingfei Chai; Fraser I. Hill; Edmund Cheung; Wietz Botes; Francois Saulnier-Troff; Colin T. McDermott; Vanessa R. Barrs (Journal of Fungi, 2024)
Dermatophytic pseudomycetoma (DPM) is a rarely reported invasive fungal infection of humans and animals, especially cats. This study aimed to identify dermatophytes, breed associations, and the frequency of extracutaneous (EC) involvement in feline DPM. Electronic records and formalin-fixed paraffin-embedded tissue (FFPET) from 32 suspected DPM cases in 30 cats were retrieved from a diagnostic laboratory between 2018 and 2024. To confirm DPM and molecular identity, DNA was extracted from FFPET for ITS2 sequencing, and immunohistochemistry was performed on PCR-negative cases. All cases were confirmed as DPM. Microsporum canis was the only dermatophyte identified. The sensitivity and specificity of ITS2 sequencing for M. canis identification in FFPET were 22/32 (68.8%) and 21/22 (95.5%), respectively. Exotic (36.7%) and Persian (23.3%) but not British breeds (26.3%) were over-represented compared to feline admissions at an affiliated veterinary hospital (8.5%, p < 0.001; 3%, p < 0.001; 21.6%, p = 0.817, respectively). Five cases (16.7%) had EC lesions; two had intra-abdominal masses; two had oral cavity masses, including one which extended into the cranial vault; and one had superficial cervical lymph node invasion. Exotic and Persian breeds are over-represented for DPM and M. canis is the primary cause. EC lesions of DPM may occur more commonly than previously thought.